In utero exposure to venlafaxine, a serotonin–norepinephrine reuptake inhibitor, increases cardiac anomalies and alters placental and heart serotonin signaling in the rat. Issue 12 (7th July 2016) - Laurent, Laetitia; Huang, Chunwei; Ernest, Sheila R.; Berard, Anick; Vaillancourt, Cathy; Hales, Barbara F.
Abstract : Background: Human studies are inconsistent with respect to an association between treatment with selective serotonin and serotonin–norepinephrine reuptake inhibitors (SSRI/SNRIs) and an increase in the incidence of congenital heart defects. Here we tested the hypothesis that in utero exposure to venlafaxine, a highly prescribed SNRI, increases the incidence of fetal heart defects and alters placental and fetal heart serotonin signaling in the rat. Methods: Timed‐pregnant Sprague Dawley rats were gavaged daily with venlafaxine hydrochloride (0, 3, 10, 30, or 100 mg/kg/day) from gestation day 8 to 20. On gestation day 21, fetuses were examined for external and internal malformations; placentas and fetal hearts were collected for the analysis of gene expression. Results: Venlafaxine had no effect on the number of live fetuses, fetal body weights, or external morphology in the absence of maternal toxicity. However, venlafaxine significantly increased the placental index (fetal body/placental weight ratio) and the incidence of fetal cardiac anomalies. Venlafaxine exposure decreased placental expression of the serotonin transporter (SERT/ Slc6a4 ) at the transcript and protein levels. In contrast, venlafaxine increased SERT expression in the hearts of female, but not male, fetuses. Expression of the serotonin 2B receptor (5‐HT2B / Htr2b ) and of fibroblast growth factor 8 was induced in fetal hearts. Conclusion: In utero venlafaxine exposure altered the placental index and induced fetal cardiac anomalies in rats. We propose that the increased incidence of cardiac anomalies is mediated through alterations in serotonin signaling in the placenta and fetal heart. Birth Defects Research (Part A), 2016. © 2016 Wiley Periodicals, Inc. Birth Defects Research (Part A) 106:1044–1055, 2016. © 2016 Wiley Periodicals, Inc.